2001
DOI: 10.1097/00043426-200106000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prognostic Significance of Intratumoral Angiogenesis in Nonmetastatic Osteosarcoma

Abstract: Intratumoral neovascularization determined at diagnosis does not correlate with long-term outcome in patients with nonmetastatic osteosarcoma. A prospective study is necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
0
27
1
2
Order By: Relevance
“…A smaller series of 29 pediatric patients with nonmetastatic osteosarcoma treated at a single institution evaluated microvessel density using CD34 staining. 30 Microvessel density did not differ between patients who survived and patients who died from osteosarcoma. These 3 conflicting reports highlight the difficulty in drawing conclusions from subjective measures of angiogenesis, particularly in the setting of different microvessel stains between studies.…”
Section: Skeletal Sarcomasmentioning
confidence: 85%
“…A smaller series of 29 pediatric patients with nonmetastatic osteosarcoma treated at a single institution evaluated microvessel density using CD34 staining. 30 Microvessel density did not differ between patients who survived and patients who died from osteosarcoma. These 3 conflicting reports highlight the difficulty in drawing conclusions from subjective measures of angiogenesis, particularly in the setting of different microvessel stains between studies.…”
Section: Skeletal Sarcomasmentioning
confidence: 85%
“…Numerous studies have indicated that VD may be of Unlike carcinomas, the situation is less clear for sarcomas where VD may not correlate with outcome. [29][30][31][32] However, our preliminary examination of VD in 29 osteosarcoma samples neither revealed any correlation with tumor progression (primary vs metastasis) nor with vWF expression. The lack of correlation between VD and vWF expression is not surprising given that vWF expression is affected by numerous factors including vessel type and size, tissue microenvironment, and angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This exclusion was performed due to incongruent data on the prognosis of these patients (21)(22)(23)(24). Moreover, another study excluded patients with chondroblastic osteosarcoma because cartilaginous stroma was described to be associated with hypovascularity (8).…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of angiogenesis in osteosarcoma still remains a matter of debate. Whereas one report by Wang et al (7) showed evidence for decreased overall survival in osteosarcoma patients with high MVD, Mantadakis et al (8) failed to demonstrate a correlation between intratumoral neovascularization and long-term outcome in patients with nonmetastatic osteosarcoma. Experimental studies on the role of tumor MVDs revealed a significant correlation between MVD and pulmonary metastasis (9).…”
Section: Introductionmentioning
confidence: 97%